2014
DOI: 10.5765/jkacap.2014.25.4.217
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Trauma due to Sexual Violence on Psychopathology and Quality of Life in Children and Adolescents

Abstract: Objectives:This study was conducted in order to investigate the influence of sexual trauma on the psychopathology and quality of life of children and adolescents in Korea.Methods:Twenty-seven children and adolescents and their caretakers who visited the Kangwon Sunflower Center participated in a cross-sectional study. Participants completed the Korean version of Kiddie-Schedule for Affective Disorders and SchizophreniaPresent and Lifetime Version, Child Behavior Checklist (CBCL), and Child Health Questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Therefore, sexually abused children had significantly higher scores for internalization, total problem behavior, anxiety/depression, externalization, withdrawal/depression (withdrawn), attention problems, thought problems, social immaturity, somatic symptoms, aggressive behavior, rule-breaking behavior (delinquency), and other problems than those in the control group. These findings were partially consistent with the results of previous studies, [ 17 , 18 , 22 ] which suggested that sexually abused children reported various psychopathologies, which included psychological distress, compared with non-abused children. Furthermore, the K-CBCL could effectively assess them.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, sexually abused children had significantly higher scores for internalization, total problem behavior, anxiety/depression, externalization, withdrawal/depression (withdrawn), attention problems, thought problems, social immaturity, somatic symptoms, aggressive behavior, rule-breaking behavior (delinquency), and other problems than those in the control group. These findings were partially consistent with the results of previous studies, [ 17 , 18 , 22 ] which suggested that sexually abused children reported various psychopathologies, which included psychological distress, compared with non-abused children. Furthermore, the K-CBCL could effectively assess them.…”
Section: Discussionsupporting
confidence: 92%
“…Only few compared the CBCL scores of victims of sexual violence with those of control groups. Kim et al [ 17 ] compared the CBCL scale results of 27 sexually abused children and adolescents who visited a local Sunflower Center (Sexual Violence Victims Integrated Support Center) and 27 control participants and found that the victims of sexual abuse showed significantly higher T-scores in withdrawal, social problems, delinquency, externalizing problems, and total problem behavior scales than the control group. They also had a statistical trend toward higher scores on the anxiety/depression and attention problems scales than did the control group.…”
Section: Introductionmentioning
confidence: 99%